W jakim zakresie gospodarka krajów zachodnich powinna być poddana poszerzonej kontroli państwa? - Tinbergen, Jan (Wydział Prawa i Administracji UAM, 1981)
In Western economies the role of the state was minimal in the early phases of industrialization. The old liberalist doctrine was that the maximum of social welfare would automatically be attained if every individual strove for maximum personal welfare. Subsequent economic thinking as well as experience have taught that this applies under very restrictive conditions only. Correspondingly an increasing number of tasks have been assumed by the state, of which a series of examples are given. This is not the end; new tasks are now seen as a consequence of pollution, especially by the development of motor traffic, of the chemical industries and as a consequence of the claim of workers to more industrial democracy. Recently the process of inflation has added the need for control of incomes so as to make income distribution more equitable. Examples are given of the instruments the Netherlands government has now been given by parliament in order to control high incomes. In addition a cultural crisis prevails requiring a stricter application of existing law and new educational policies. Moreover the establishment of the new international order will add new obligations to national governments. Such new obligations may be created by treaties concluded in order to further the development of low-income countries, to reduce the danger of pollution, of overfishing, etc. International taxes may be among the new instruments of national development policies. With the increase in state tasks the danger of overbureaucratization — already expressed in „Parkinson's law" — will grow further. Structural changes will be needed in order to reduce this danger. Generally speaking decentralization of a number of activities is needed; in other words, delegation of tasks to lower hierarchical levels. Another way of reducing the degree of bureaucracy is the simplification of unnecessarily complicated regulations, for instance in social insurance or assistance systems.
To What Extent Should the Economy be Controlled Through an Expansion of the Functions of the State in Western Countries?